2023
DOI: 10.21203/rs.3.rs-2410384/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasmepsin X activates function of the PCRCR complex in P. falciparum by processing PfRh5 for binding to basigin and invasion of human erythrocytes

Abstract: Plasmodium falciparum causes the most severe form of malaria in humans. The protozoan parasite develops within erythrocytes to mature schizonts, that contain more than 16 merozoites, which egress and invade fresh erythrocytes. The aspartic protease plasmepsin X (PMX), processes proteins and proteases essential for merozoite egress from the schizont and invasion of the host erythrocyte, including the leading vaccine candidate PfRh5. PfRh5 is anchored to the merozoite surface through a 5-membered complex (PCRCR)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Individual mAbs were characterized: clone R5.004 was found to be strongly neutralizing and to bind directly to the basigin-binding site of PfRH5 [4]; whilst clone R5.008 was found to be moderately neutralizing possibly by hindering PfRH5’s access to basigin through steric clashes with the RBC membrane or basigin’s RBC binding partners PCMA or MCT1 (S1 Fig A and B) [4, 25]. It has recently been discovered that PfRH5 must have its pro-sequence cleaved by plasmepsin X before it can engage basigin [26].…”
Section: Resultsmentioning
confidence: 99%
“…Individual mAbs were characterized: clone R5.004 was found to be strongly neutralizing and to bind directly to the basigin-binding site of PfRH5 [4]; whilst clone R5.008 was found to be moderately neutralizing possibly by hindering PfRH5’s access to basigin through steric clashes with the RBC membrane or basigin’s RBC binding partners PCMA or MCT1 (S1 Fig A and B) [4, 25]. It has recently been discovered that PfRH5 must have its pro-sequence cleaved by plasmepsin X before it can engage basigin [26].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, one study found anti-P113 antibodies that block the interaction with RH5-Nt are GIA-negative 34 , whilst another reported P113 plays an important role in maintaining normal architecture of the parasitophorous vacuole membrane within the infected erythrocyte 35 . Moreover, it has since been reported that RH5-Nt is cleaved off the RH5 molecule within the micronemes of the P. falciparum parasite by the aspartic protease plasmepsin X prior to release of RH5 to the merozoite surface 36 , suggesting it would be an unlikely target of antibodies. In summary, these data strongly suggest these regions of disorder within RH5_FL are not targets of functional IgG.…”
Section: Discussionmentioning
confidence: 99%